The Relationship Between the Duration of Cimino Arteriovenous Fistula Use and Quality of Life Among Hemodialysis Patients - Sihar Ida Tampubolon; Sabina Gero; Amrih Widiati; Eko Winarto (Indonesian Journal of Global Health Research, 2026)
Chronic Kidney Disease (CKD) is a global health problem with increasing prevalence. Hemodialysis uses Cimino AV shunt as the patient’s lifeline, but complications and duration of use are suspected to affect quality of life. This quantitative cross sectional study aimed to determine the relationship between duration of Cimino AV use and quality of life in hemodialysis patients at EMC Cikarang Hospital, West Java. A population of 120 CKD hemodialysis patients with a sample of 55 respondents was selected by purposive sampling using Slovin formula. The independent variable, duration of Cimino AV use, was obtained from medical records, while the dependent variable, quality of life, was measured using SF-36 questionnaire. The validity and reliability of the questionnaire had been tested, confirming that the instrument was valid and reliable for use in this study.Data were analyzed using Fisher’s Exact Test and Multiple Logistic Regression with p-value 50 years old 56.4%, male 63.6%, and had high school education 65.4%. Good quality of life was found in 65.4% respondents. Duration of Cimino AV use of 24-60 months was dominant 56.5%. There was a significant relationship between duration of Cimino AV use and quality of life p=0.001. Duration of Cimino AV use was the dominant factor OR = 8.54 after controlling for age, education, occupation, marital status, and gender. Longer duration of Cimino AV use is significantly associated with better quality of life in hemodialysis patients.